Functional Profiling Reveals Altered Metabolic Activity in Divers’ Oral Microbiota During Commercial Heliox Saturation Diving - Monnoyer, Roxane; Eftedal, Ingrid; Hjelde, Astrid; Deb, Sanjoy; Haugum, Kjersti; Lautridou, Jacky (Frontiers in Physiology, 2021)
Background: The extreme environment in saturation diving affects all life forms, including the bacteria that reside on human skin and mucosa. The oral cavity alone is home to hundreds of different bacteria. In this study, we examined the metabolic activity of oral bacteria from healthy males during commercial heliox saturation diving. We focused on environmentally induced changes that might affect the divers’ health and fitness. Methods: We performed pathway abundance analysis using PICRUSt2, a bioinformatics software package that uses marker gene data to compute the metabolic activity of microbial communities. The analysis is based on 16S rRNA metagenomic data generated from the oral microbiota of 23 male divers before, during, and after four weeks of commercial heliox saturation diving. Environmentally induced changes in bacterial metabolism were computed from differences in predicted pathway abundances at baseline before, versus during and immediately after saturation diving. Results and conclusion: The analysis predicted transient changes that were primarily associated with the survival and growth of bacteria in oxygenated environments. There was a relative increase in the abundance of aerobic metabolic pathways and a concomitant decrease in anaerobic metabolic pathways, primarily comprising of energy metabolism, oxidative stress responses, and adenosylcobalamin biosynthesis. Adenosylcobalamin is a bioactive form of vitamin B12 (vitB12), and a reduction of vitB12 biosynthesis may hypothetically disturb the divers’ physiology. While host effects of oral bacterial vitamin metabolism are uncertain, this is a finding that concurs with the existing recommendations for vitB12 supplements as part of the divers’ diet, whether to boost antioxidant defenses in bacteria or their host, or to improve oxygen transport during saturation diving.